Synonymy between Lymnaea bogotensis Pilsbry, 1935 and Lymnaea cousini Jousseaume, 1887 (Gastropoda: Lymnaeidae) (2006)
ABSTRACT: The lymneid snail Lymnaea bogotensis Pilsbry 1935 is synonymized with L. cousini Jousseaume 1887, based on morphological comparisons of the reproductive systems. The shell, renal tube, and reproductive system are described and illustrated from specimens collected in the type locality and the municipality of Paipa, Colombia. Bibliographical records reveal L. columella to be the commonest lymneid in the country. The latter two species can be differentiated based on the morphology of the penial complex.